2021
DOI: 10.4018/978-1-7998-3257-7.ch006
|View full text |Cite
|
Sign up to set email alerts
|

FinTech in Banks

Abstract: There has been an extensive boost in the use of FinTech in the Banking sector during the last few years. This chapter provides a comprehensive overview of the new opportunities offered by FinTech to the banking sector, its prospective risks, and the possible challenges to be faced in its adaptation. The authors propose that the new opportunities of FinTech include better digital banking experience, personalized customer services, high-level data security, cost-effective, and efficient services. On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Moreover, the size of the bank has a negative coefficient and significant at 1 percent, this highlights that the larger the bank the higher the cost associated with its operations and this affect the profitability negatively Ebrahim et al (2020). Lastly, the growth of the bank is found to be insignificant.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the size of the bank has a negative coefficient and significant at 1 percent, this highlights that the larger the bank the higher the cost associated with its operations and this affect the profitability negatively Ebrahim et al (2020). Lastly, the growth of the bank is found to be insignificant.…”
Section: Resultsmentioning
confidence: 90%
“…However, Du and Liu (2022) argue that FinTech does not only bring opportunities but challenges as well. Ebrahim et al (2020) argued that some of the possible opportunities brought by FinTech are an improved banking experience, customized customer service, security of data and efficiency. They, however, argue that the risk of security still exists within the FinTech world.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have explored the relationship between banking and fintech, including those by Deng et al (2021) and Zhao et al (2019), and some have identified factors that influence the use of fintech, such as Al Nawayseh (2020) and Ebrahim et al (2021). While the use of fintech posed challenges for clients of commercial banks and MFIs in both rural and urban areas in normal circumstances, the Covid-19 pandemic has had a mixed impact on the financial sector, as Chen et al (2021) have suggested.…”
Section: Problem Statementmentioning
confidence: 99%
“…Meanwhile, the fragility of cyber security, weak regulatory of Fintech, high competition of Fintech companies, customer trust, decrease in market share and increase in customer churn rate are the fundamental challenges of Fintech adaption (Saba, Kouser & Chaudhry, 2019). These statements supported by Ebrahim, Kumaraswamy & Abdulla,(2020); Rahman, Rahiman, Meero & Amin, (2022)where the studies figured out the responsiveness of financial institutions towards new adaptation of Fintech advancement, cyber-attack problem, Fintech regulation, maintaining the talented staffs and unskilled staffs are among the challenges encountered by financial institutions. In the meantime, the regulatory environment and regulation of Fintech are the critical challenges faced in the industry and therefore, review, innovate and enact the new existing regulatory framework to ensure the modern technology is compatible with the transactions including its transparency and disclosure (Islamic Financial Services Board, 2017).Besides that, according to Yateem, (2019), the Islamic financial industry encountered some challenges in adopting Fintech such as unsophisticated staffs and clients, financial risks on a huge amount of transaction, highly competitive with Fintech companies, breach of data privacy that led to the cybercriminal, and uncontrollable regulation if it is beyond the regulatory boundaries in the event money laundering.…”
Section: Challenges Of Fintech Application In Islamic Financial Industrymentioning
confidence: 99%
“…Unskilled staff in the Fintech field can cause the wrong key in data, wrong financial data transfer, incorrect account calculation, and unable to explain the digital services to the clients. Nevertheless, strong IT skills and skilled staffs help to improve the performance of a financial institution but maintaining them in the institution is one of the challenges (Ebrahim et al, 2020). Hence, the employers must provide a good salary and comfortable workplace to maintain the talented staff in the institution.…”
Section: Human Resourcesmentioning
confidence: 99%